VLF wave amplification by wave-particle interaction - Singh R.N.; Singh R.P. (My University, 2025)
A charged particle beam is assumed to move through the magnetosphere. It is shown that the VLF waves propagating at non-zero angles with the beam are amplified. © 1971.